Peripheral blood sCD3− CD4+ T cells: a useful diagnostic tool in angioimmunoblastic T cell lymphoma. Issue 1 (24th June 2013) - Singh, Anju; Schabath, Richard; Ratei, Richard; Stroux, Andrea; Klemke, Claus‐Detlev; Nebe, Thomas; Flörcken, Anne; van, Antje; Anagnostopoulos, Ioannis; Dörken, Bernd; Ludwig, Wolf‐Dieter; Pezzutto, Antonio; et al.
Abstract Angioimmunoblastic T cell lymphoma (AITL) belongs to the subgroup of mature T cell lymphomas according to the World Health Organization and is one of the common T cell lymphomas in Western countries. Particularly in cases in which histological confirmation cannot be easily achieved, immunophenotyping of peripheral blood can give important information for the differential diagnosis of AITL. sCD3− CD4+ T cells are a typical feature of AILT in flow cytometry of peripheral blood. In this retrospective study, the diagnostic value of flow cytometry for the diagnosis 'AITL' was assessed by comparing the frequency of sCD3− CD4+ T cells in leukemic AITL patients and in patients with other leukemic CD4+ T cell lymphomas. Immunophenotyping of peripheral blood by flow cytometry was performed in a lymphocyte gate using fluorochrome‐labelled antibodies against CD3, CD2, CD4, CD5, CD7, CD8, CD10, CD14, CD16, CD19, CD56, CD57 and T cell receptor. In 17/17 leukemic AITL patients, a small but distinct population of sCD3− CD4+ T cells was detected (mean percentage of sCD3− CD4+ T cells in the lymphocyte gate: 11.9 ± 15.4%, range 0.1–51.8%). In contrast, sCD3− CD4+ T cells were found in only 1/40 patients with other leukemic CD4+ T cell lymphomas (one patient with mycosis fungoides). sCD3− CD4+ T cells have a high positive predictive value (94%) for the diagnosis 'AITL'. Flow cytometry is particularly useful in the differential diagnosis of AITL, even if the aberrant T cell population has a very low frequency. Further biological characterization of this subfraction of lymphoma cells is warranted. Copyright © 2013 John Wiley & Sons, Ltd.